Data-Driven Decision Making for School Improvement in the Indonesian Context: A Literature Review - Nurkolis Nurkolis; Widia Kusumaningsih (Pedagogi: Jurnal Ilmu Pendidikan, 2026)
This literature review examines the application of data-driven decision making (DDDM) for school improvement within the specific context of Indonesia. It examines the theoretical foundations, empirical evidence, and practical considerations related to implementing DDDM in educational settings. The review synthesizes research from various sources, including journal articles, book chapters, and proceedings published within the last 15 years, to provide a comprehensive overview of the current state of knowledge. The analysis focuses on key themes, including the role of leadership, the importance of data literacy, the impact of technology, and the cultural considerations relevant to the Indonesian educational landscape. The aim is to identify best practices, highlight gaps in the existing literature, and suggest directions for future research aimed at enhancing the effectiveness of DDDM in improving educational outcomes in Indonesia.